Utilization of tempe dregs for the growth of tilapia fish (Oreochromis niloticus) - Maulit, Julham; Rakhfid, Abdul; Budiyanti, Budiyanti; Karyawati, Karyawati; Rochmady, Rochmady (Sangia Research Media and Publishing, 2024)
The objective of this study is to determine the impact of feeding tempeh dregs at varying doses on tilapia growth and survival (Oreochromis niloticus). The study was conducted from March to May 2023 in Wataliku Village, Kabangka District, Muna Regency. The study employed a completely randomized design with four treatments that involved the administration of tempeh dregs in the diet. These were designated as follows: treatment A (control) was commercial feed; treatment B was 10% tempeh dregs; treatment C was 15% tempeh dregs; and treatment D was 20% tempeh dregs. Each treatment was replicated three times. The data were subjected to analysis of variance (ANOVA) at a confidence level of 95% (α0.05). The study results demonstrated that the highest specific growth was observed with the addition of 20% tempe dregs, with an average of 2.97% per day. This was followed by 15% tempe dregs (2.47% per day), 10% tempe dregs (2.28% per day), and commercial feed (2.00% per day). The highest absolute growth was observed in the treatment that included 20% tempe dregs, with an average of 1.04 g per individual. This was followed by the treatment that included 15% tempe dregs (0.87 g per individual), the treatment that included 10% tempe dregs (0.80 g per individual), and the treatment that included commercial feed (0.00 g per individual). It should be noted that survival was 100% in all treatments. Analysis of variance (α0.05) demonstrated that administration of tempe dregs at varying doses had a statistically significant impact on the specific and absolute growth of tilapia larvae (Oreochromis niloticus).